Predictive factors of mortality in patients with idiopathic pulmonary fibrosis treated with antifibrotics: a novel prognostic scoring system - Polat, Gülru; Özdemir, Özer; Ermin, Sinem; Serçe Unat, Damla; Demirci Üçsular, Fatma (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Any test that provides sufficient prognostic information to guide treatment decisions in idiopathic pulmonary fibrosis (IPF) is not available. The aim of our study was to determine the predictive factors of mortality in patients with IPF treated with antifibrotics. Methods: Patients with diagnosis of IPF who were treated with antifibrotics between 2016 – 2021 were included in the study. Demographic, clinical and laboratory characteristics of the patients was derived from hospital records retrospectively. Kaplan Meier and multivariate cox regression analysis were achieved for detection of mortality predictors. Results: Study population was composed of 119 IPF patients with a male predominance of 80.7% (n=96). Mean age of the patients was 67.9 ± 7.07 years. On univariate analysis, sex was not a significant predictor of mortality (HR 1.79; 95% CI: 0.87 – 3.69, p =0.11).  BMI ≤ 26,6 m2/kg, DLCO ≤ 3.11 ml/mmHg/min, age over 62 years, 6DWT ≤ 382 meters, NLR ≤ 2.67 and PDW ≤ 16.7% were found to be significant for predicting mortality. On multivariate cox regression analysis four parameters remained significant for prediction of mortality: RDW > 14%, NLR ≤ 2.67, BMI ≤ 26,6 m2/kg and DLCO ≤ 3.11 ml/mmHg/min (respectively, HR: 2.0. 95% CI: 1.02 – 3.91, p=0.44; HR: 2.68. 95% CI: 1.48 – 4.85, p=0.001, HR: 2.07. 95% CI: 1.14 – 3.76, p=0.02, HR: 3.46. 95% CI: 1.85 – 6.47, p